Influence of elevated Nd fluxes on the northern Nd isotope end member of the Atlantic during the early Holocene - Pöppelmeier, Frerk; Scheen, Jeemijn; Blaser, Patrick; Lippold, Jörg; Gutjahr, Marcus; Stocker, Thomas F. (Paleoceanography and paleoclimatology, 2020)
The neodymium (Nd) isotopic composition of seawater is a valuable tool for the reconstruction of past water mass provenance and hence deep water geometry. A meaningful interpretation of Nd isotope down-core records requires knowledge of potential variations of water mass end member characteristics. While often assumed temporally constant, recent investigations revealed glacial-interglacial variability of the northern and southern Nd isotope end members in the Atlantic. These new constraints have a strong influence on the interpretation of the Atlantic deep water mass evolution, yet the processes responsible for the end member shifts remain uncertain. Here we combine a new compilation of Atlantic Nd isotope reconstructions of the early Holocene with the Nd-enabled Bern3D model to quantify the recently proposed hypothesis of a northern Nd isotope end member shift during the early Holocene. We achieve the best model-data fit with a strong increase of the Nd flux in the northern high latitudes by a factor of 3 to 4, which lowers the northern end member signature by about 1 ε-unit. Our findings thus agree with the rationale that glacially weathered material entered the northern Northwest Atlantic after the ice sheets retreated late in the deglaciation and released substantial amounts of unradiogenic Nd as suggested previously. Further, we find that variations in the strength of the Atlantic Meridional Overturning Circulation (AMOC) cannot reproduce the observed Nd isotope excursions of the compiled data, ruling out an early Holocene AMOC “overshoot.”